PELAKSANAAN MEDIASI SENGKETA KONSUMEN OLEH BADAN PENYELESAIAN SENGKETA KONSUMEN SEBAGAI WUJUD PERLINDUNGAN HUKUM BAGI KONSUMEN - Candra Dewi, Ni Putu; Pujawan, I Made (Kertha Wicara : Journal Ilmu Hukum; Vol. 01, No. 04, September 2013)
Consumers are part of Indonesian society has right to be protected. Through Consumers Protection Act, the Government has set up the protection. However, few consumers who knew and understand the law. Similiarly, the consumer alternative dispute resolution through mediation at Consumer Dispute Settlement Body.
Keywords: Protection, Consumers Disputes, Mediation, Consumer Dispute Settlement Body.